The talented Mr. Ripley - Horberg, William; Minchella, Anthony (Hollywood, CA : Paramount, 2000)
Tom Ripley is a calculating young man who believes it's better to be a fake somebody than a real nobody. He's hired to go to Italy to bring back the playboy son of a millionaire and soon is plunged into a daring scheme of duplicity, lies and murder.
Editor, Walter Murch ; executive producer, Sydney Pollack
Cast: Matt Damon, Gwyneth Paltrov, Jude Law
VCD format
Keywords: Love in motion pictures